Cultural Identity Background Toward The First Year Intercultural Communication Life Of Indonesian Phd Muslim Women Students In The USA - Win Listyaningrum Arifin (UIN Salatiga, 2022)
This study aimed at investigating first year experience of international communication life of Indonesian PhD Muslim female students in the USA deal with their cultural background. Therefore, their cultural background influenced the host community in receiving their existence in the new environment both as international students and part of the the society. This study tried to explore how far Crenshaw intersectionality theory and Ting-Toomey’s theory on intercultural communication has assisted to formulate and answer the following: (1) How far is the influence of the cultural identity background has helped the students living in a country? and (2) To what extent does intercultural communication diminish the cultural background to formulate the success of these students?This study is a qualitative approach using auto ethnography of depth interviews to picture the problems faced by the students. The study revealed that the ability to well-managed the cultural background in the circle of intercultural communication might help the success of the students both in the academic and social life.